Federal medical biological agency of Russia`s efforts to support Russian athletes during COVID-19 outbreak - Zholinsky, A. V.; Kruglova, I. V.; Feshchenko, V. S.; Risukhina, Y. V.; Fomin, A. V.; Galaktionova, N. M.; Pavlova, A. A.; Mitin, I. N.; Parastayev, S. A.; Bezuglov, E. N.; Fyodorov, A. N.; Barshak, S. I. (Sport Sciences for Health, 2022)
This paper dwells upon COVID-19-related efforts of the Center for Sports Medicine, Federal Medical and Biological Agency of Russia. The Agency has the following precautions in place: regular polymerase chain reaction (PCR) testing of athletes and staff; double PCR testing before going to training camps or medical examinations; isolating athletes and their traceable contacts when COVID is suspected; observation and isolation wards set up at training camp venues. Athlete vaccination has begun. Athletes are provided online advice on health, diet, and exercising plus special care for chronically ill athletes and remote psychological counseling. Athletes recovering from COVID-19 are offered rehabilitation programs and doctor-supervised return to training. Specialists of the Research Department at FMBA`s Center for Sports Medicine carried out a research dedicated to the prevalence of COVID-19 and different variants of its course in Russian athletes. The study period lasted from March to December 2020. A total of 27,438 records were analyzed. In May, June, July and August 2020, the percentage of positive PCR tests for athletes was significantly lower than the nationwide percentage at p < 0.05, Pearson`s chi-squared test. However, the differences were nullified by September-October. The disease was mild or asymptomatic in most patients. Athletes of summer sports were found to be most likely to contract COVID-19.